La intersección cuerpo-género-violencia a través de los dibujos de niñas y niños de la ciudad de Chihuahua y Guachochi en la sierra Tarahumara. Análisis y método - Ojeda Martínez, Rosa Icela (El Colegio de México A.C., 2024)
The article addresses the relationship between the body, violence, and gender through the analysis of 111 drawings by girls and boys in the city of Chihuahua, and the municipality of Guachochi in the Sierra Tarahumara. A collaborative methodology was used, through co-participatory, playful, and artistic workshops. The analysis focused on understanding gender differences in the content of graphic works. It was found that girls and boys represent violence in a differentiated way, especially in embodied aspects such as postures and facial expression; we also found stereotyped gender traits such as clothing. All the girls except one depicted female characters wearing dresses or skirts, their bodies in passive and submissive postures in the face of aggression; on the contrary, male children seem to identify more with the figure of the aggressor, and they always drew the aggressors as masculine characters who can use weapons and even commit murder. In conclusion, it is proposed that interrelated cultural consensuses exist between gender performativity, the ways in which violence is practiced and the expression of corporeity, which are recognized and internalized from childhood.